Structure and variability of the North Icelandic Jet from two years of mooring data - Huang, Jie; Pickart, Robert S.; Valdimarsson, Héðinn; Lin, Peigen; Spall, Michael A.; Xu, Fanghua (Journal of Geophysical Research: Oceans, 2019)
Author Posting. © American Geophysical Union, 2019. This article is posted here by permission of American Geophysical Union for personal use, not for redistribution. The definitive version was published in Journal of Geophysical Research-Oceans 124(6), (2019): 3987-4002, doi:10.1029/2019JC015134. Mooring data from September 2011 to July 2013 on the Iceland slope north of Denmark Strait are analyzed to better understand the structure and variability of the North Icelandic Jet (NIJ). Three basic configurations of the flow were identified: (1) a strong separated East Greenland Current (EGC) on the mid‐Iceland slope coincident with a weak NIJ on the upper slope, (2) a merged separated EGC and NIJ, and (3) a strong NIJ located at its climatological mean position, coincident with a weak signature of the separated EGC at the base of the Iceland slope. Our study reveals that the NIJ‐dominant scenario was present during different times of the year for the two successive mooring deployments—appearing mainly from September to February the first year and from January to July the second year. Furthermore, when this scenario was active it varied on short timescales. An energetics analysis demonstrates that the high‐frequency variability is driven by mean‐to‐eddy baroclinic conversion at the shoreward edge of the NIJ, consistent with previous modeling work. The seasonal timing of the NIJ dominant scenario is investigated in relation to the atmospheric forcing upstream of Denmark Strait. The resulting lagged correlations imply that strong turbulent heat fluxes in a localized region on the continental slope of Iceland, south of the Spar Fracture zone, lead to a stronger NIJ dominant state with a two‐month lag. This can be explained dynamically in terms of previous modeling work addressing the circulation response to dense water formation near an island. The authors thank the crew members of the R/V Knorr, RRS James Clark Ross, and R/V Bjarni Sæmundsson for the deployment and recovery of the moorings. D. Torres and F. Bahr ...